SOSIALISASI FISIOTERAPI DENGAN PEMBERIAN NERVE DAN TENDON GLIDING EXERCISE UNTUK PENCEGAHAN TERJADINYA CARPAL TUNNEL SYNDROME PADA IBU RUMAH TANGGA DI KAMPUNG SUKAGALIH RT05 RW06 KECAMATAN UJUNG BERUNG KOTA BANDUNG - Ika Rahman; Muhamad Hasan AL Askari; Fauziyyah Kurnia Putri; Caessario Stephan (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
Carpal tunnel syndrome (CTS) is a disease caused by repeated flexion and extension movements that cause the median nerve (median nerve) to be pinched by the transverse carpal ligament/carpal ligament so that the hand feels uncomfortable when working (painful, tingling/numbness). Typical symptoms include pain, paresthesias, numbness, or tingling after healing from the median nerve area of the hand, usually tingling in the thumb on the radial side of the index finger, middle, and ring finger. One of the ways to reduce and prevent complaints of carpal tunnel syndrome is with Nerve and Tendon Gliding Exercise. The goal is to reduce pressure on the median nerve at the wrist so that the symptoms caused can gradually progress well and optimize the function activities in the patient's hand. The result of this activity is that housewives gain new knowledge about carpal tunnel syndrome and state that this activity is very beneficial for them and quite helpful in reducing CTS complaints.Keywords: carpal tunnel syndrome, nerve and tendon gliding exercise, housewife